Nepal : 2008 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Nepal. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Limited progress has been made in addressing Nepal's structural weaknesses in tax administration and public financial management. Macroeconomic performance under the recent Poverty Reduction and Growth Facility (PRGF)-supported program has been stable. The outlook for 2007-08 remains stable. Although the macroeconomic performance has been stable, progress on structural reforms has been held back by the fragile political circumstances. Public enterprises and the Nepal Oil Corporation, in particular, pursue quasi-fiscal activities involving significant subsidies. Nepal's growth prospects depend most importantly on a peaceful political transition.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet